Psychological Impact of the COVID-19 Outbreak on Nurses in China: A Nationwide Survey During the Outbreak - Liu, Yan; Long, Youlin; Cheng, Yifan; Guo, Qiong; Yang, Liu; Lin, Yifei; Cao, Yu; Ye, Lei; Jiang, Yan; Li, Ka; Tian, Kun; A, Xiaoming; et al. (Frontiers in Psychiatry, 2020)
Background: The COVID-19 pandemic is a major public health issue and challenge to health professionals. In similar epidemics, nurses experienced more distress than other providers. Methods: We surveyed both on-duty nurses caring for infected patients and second-line nurses caring for uninfected patients from Hubei and other provinces throughout China. Results: We received completed surveys from 1364 nurses from 22 provinces: 658 front-line and 706 second-line nurses. The median (IQR) GHQ-28 score of all nurses was 17 (IQR 11 to 24). The overall incidence of mild-to-moderate distress (GHQ score >5) was 28%; that for severe distress (GHQ score >11) was 6%. The incidence of mild-to-moderate distress in the second-line nurses was higher than that in the front-line nurses (31% vs. 25%; OR, 0.74; 95 CI, 0.58 to 0.94). Living alone (OR, 0.62; 95% CI, 0.44 to 0.86) and feeling supported (OR, 0.82, 95% CI, 0.74 to 0.90) independently predicted lower anxiety. Conclusions: During the COVID-19 pandemic, the psychological problems of all nurses were generally serious. The interviewed second-line nurses face more serious issues than the front-line nurses.